2001
DOI: 10.1002/nbm.681
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization transfer MRS

Abstract: This review deals with magnetization transfer (MT) effects observed in in vivo NMR spectroscopy. The basic experimental methods of MT experiments, the underlying kinetic mechanisms as well as the evaluation of measured data by fits to two-or three-pool models are described. Experimental results of both 31 P and 1 H in vivo MRS are reviewed showing the potential of MT experiments to characterize kinetic equilibrium reactions. This includes reactions where all involved components are MR visible, as well as situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 65 publications
2
82
0
Order By: Relevance
“…[41][42][43] MT-MRS is discussed further in the article by D. Leibfritz and W. Dreher in this issue. 44 It is still possible that this effect will have significant application in understanding tissue metabolism in the future. period, researchers have characterized the underlying NMR physics, exchange and relaxation rates that govern MT, although detailed understanding of the chemistry and molecular interactions is still needed.…”
Section: Applications In Imagingmentioning
confidence: 99%
“…[41][42][43] MT-MRS is discussed further in the article by D. Leibfritz and W. Dreher in this issue. 44 It is still possible that this effect will have significant application in understanding tissue metabolism in the future. period, researchers have characterized the underlying NMR physics, exchange and relaxation rates that govern MT, although detailed understanding of the chemistry and molecular interactions is still needed.…”
Section: Applications In Imagingmentioning
confidence: 99%
“…Magnetization transfer phenomena in skeletal muscle have also been investigated with 1 H MRS. These studies were inspired by the remarkable finding in 1 H MRS studies of rat brain by Leibfritz and colleagues (110,111) that off-resonance saturation leads to a strong reduction in the PCr/Cr proton signal. Subsequently, De Graaf et al (112) demonstrated that other metabolites in rat brain, including glutamate/glutamine and lactate, also exhibit a significant off-resonance MT effect.…”
mentioning
confidence: 99%
“…In vivo fluxes between PCr and ATP in rat brain and skeletal muscle were quantified using MT in the 1980s (112). Since then, this technique has been widely applied to measure CK reaction rate in heart, brain, and skeletal muscle (17,73,(112)(113)(114)(115)(116)(117). P i -to-ATP flux has also been investigated in liver, heart, Quant Imaging Med Surg 2017;7(6):707-726 qims.amegroups.com brain, and skeletal muscle (17,(118)(119)(120)(121).…”
mentioning
confidence: 99%